Implementation of Strategic Interventions for Managing Hallucinations among Patients at dr. H. Marzoeki Mahdi Psychiatric Hospital - Fajar, Nur Fajariyah; Safira, Siti (Blambangan Journal of Community Services (BJCS), 2025)
Background: Schizophrenia is a chronic mental disorder characterised by hallucinations that impair daily functioning. Hallucinations are false sensory perceptions without external stimuli, causing clients difficulty in distinguishing internal experiences from reality. Nursing intervention strategies are essential to help clients recognise and control hallucinatory symptoms. Aim: To analyse the effectiveness of nursing intervention strategies for managing hallucinations in clients with schizophrenia at PKJN dr. H. Marzoeki Mahdi Hospital. Implementation: Nursing care was performed three times over three days for 10- 15 minutes. Nursing interventions provided to clients with the primary nursing problem of auditory hallucinations are implemented through strategies for managing hallucinations. Results: to clients with the primary nursing problem of auditory hallucinations are implemented through strategies for managing hallucinations. Conclusion and suggestion: Hallucination management strategies are effective in reducing auditory hallucinations in clients with schizophrenia and should be applied as standard nursing interventions in psychiatric care.